Functional analysis of CTLA4 promoter variant and its possible implication in colorectal cancer immunotherapy - Angulo-Aguado, Mariana; Orjuela-Amarillo, Sarah; Mora-Jácome, Julián Francisco; Córdoba, Lea Paloma; Gallego-Ortiz, Antonio; Gaviria-Sabogal, Cristian Camilo; Contreras, Nora; Figueroa, Carlos; Ortega-Recalde, Oscar; Morel, Adrien; Fonseca-Mendoza, Dora Janeth (Frontiers in Medicine, 2023)
Background: Colorectal cancer (CRC) is a prevalent cancer, ranking as the third most common. Recent advances in our understanding of the molecular causes of this disease have highlighted the crucial role of tumor immune evasion in its initiation and progression. CTLA4, a receptor that acts as a negative regulator of T cell responses, plays a pivotal role in this process, and genetic variations in CTLA4 have been linked to CRC susceptibility, prognosis, and response to therapy. Methods: We conducted a case-control study involving 98 CRC patients and 424 controls. We genotyped the CTLA4 c.-319C>T variant (rs5742909) and performed an association analysis by comparing allele frequencies between the patients and controls. To assess the potential functional impact of this variant, we first performed an In Silico analysis of transcription factor binding sites using Genomatix. Finally, to validate our findings, we conducted a luciferase reporter gene assay using different cell lines and an electrophoretic mobility shift assay (EMSA). Results: The case-control association analysis revealed a significant association between CTLA4 c.-319C>T and CRC susceptibility (p=0.023; OR 1.89; 95% CI = 1.11-3.23). Genomatix analysis identified LEF1 and TCF7 transcription factors as specific binders to CTLA4 c.-319C. The reporter gene assay demonstrated notable differences in luciferase activity between the c.-319 C and T alleles in COS-7, HCT116, and Jurkat cell lines. EMSA analysis showed differences in TCF7 interaction with the CTLA4 C and T alleles. Conclusions: CTLA4 c.-319C>T is associated with CRC susceptibility. Based on our functional validation results, we proposed that CTLA4 c.-319C>T alters gene expression at the transcriptional level, triggering a stronger negative regulation of T-cells and immune tumoral evasion.